A novel autophagy modulator 6-Bio ameliorates SNCA/α-synuclein toxicity. Issue 7 (3rd July 2017) - Suresh, S. N.; Chavalmane, Aravinda K.; DJ, Vidyadhara; Yarreiphang, Haorei; Rai, Shashank; Paul, Abhik; Clement, James P.; Alladi, Phalguni Anand; Manjithaya, Ravi
ABSTRACT: Parkinson disease (PD) is a life-threatening neurodegenerative movement disorder with unmet therapeutic intervention. We have identified a small molecule autophagy modulator, 6-Bio that shows clearance of toxic SNCA/α-synuclein (a protein implicated in synucleopathies) aggregates in yeast and mammalian cell lines. 6-Bio induces autophagy and dramatically enhances autolysosome formation resulting in SNCA degradation. Importantly, neuroprotective function of 6-Bio as envisaged by immunohistology and behavior analyses in a preclinical model of PD where it induces autophagy in dopaminergic (DAergic) neurons of mice midbrain to clear toxic protein aggregates suggesting that it could be a potential therapeutic candidate for protein conformational disorders.